A comparison of the 2017 American College of Cardiology/American Heart Association Blood Pressure guideline and the 2017 American Diabetes Association Diabetes and Hypertension position statement for U.S. adults with diabetes - Muntner, P; Whelton, P; Woodward, M; Carey, R (American Diabetes Association, 2018)
OBJECTIVE To determine the concordance in the prevalence of hypertension and pharmacological antihypertensive treatment recommendations for U.S. adults with diabetes using definitions from the 2017 American College of Cardiology/American Heart Association (ACC/AHA) blood pressure (BP) guideline and the 2017 American Diabetes Association (ADA) diabetes and hypertension position statement. RESEARCH DESIGN AND METHODS We analyzed data for U.S. adults with diabetes in the U.S. National Health and Nutrition Examination Survey (NHANES), 2011–2016 (n = 2,266). Diabetes was defined by treatment with glucose-lowering medication, glycosylated hemoglobin ≥6.5%, fasting serum glucose ≥126 mg/dL, or nonfasting serum glucose ≥200 mg/dL. BP was measured three times and antihypertensive medication use was self-reported. RESULTS The prevalence (95% CI) of hypertension among U.S. adults with diabetes was 77.1% (73.9, 80.0) and 66.3% (63.4, 69.1) according to the ACC/AHA and ADA definitions, respectively. Also, 22.9% (20.0, 26.1) did not have hypertension according to either definition, and the concordance in hypertension status was 89.2% (87.2, 91.0). Among U.S. adults with diabetes not taking antihypertensive medication, 52.8% (47.7, 57.8) were not recommended to initiate antihypertensive medication by either the ACC/AHA or the ADA document and 22.4% (19.2, 25.9) were recommended to initiate it by both documents (overall concordance 75.2% [70.4, 79.4]). Among those taking antihypertensive medication, 45.3% (41.3, 49.4) and 50.4% (46.5, 54.2) had BP above the goal in neither and both documents, respectively (overall concordance 95.7% [93.4, 97.2]). CONCLUSIONS A high percentage of U.S. adults with diabetes are provided identical antihypertensive treatment recommendations by the ACC/AHA BP guideline and the ADA diabetes and hypertension position statement.